PROUCA: uma análise sobre a inclusão digital e as práticas de ensino de ciências em Manaus - Araújo, Andréia Paula Ferreira de (2016)
This study aimed to analyze the PROUCA as digital inclusion policy in schools in the municipality of Manaus and its contributions to the teaching practices in science. The theoretical perspective adopted placed the importance of integrating Information and Communication Technologies (ICT) in school education and the challenges of building a science education in basic education, indicating fundamentals of digital inclusion in the Brazilian context from the educational processes taking view current theoretical perspectives and objectives of teaching and learning science at school. These perspectives have led to an analysis of the possible use of new technologies, particularly the educational laptop PROUCA, as an educational resource to renew practices in science education. As for the methodological perspective, the research was based on qualitative research, validated by literature and the use of techniques such as observation, questionnaire and interview. In field research context were contacted 12 school units of the Municipal Department of Education, and, respectively, 12 science teachers from the 9th grade of elementary school (EF), and a trainer of the Center for Educational Technology (NTE) to collect data. The collected data were analyzed based on empirical and interpretative analysis. The results showed that the inclusion of PROUCA in the investigated schools did not cause profound changes in science teaching, which collected data show that the textbook, videos and slides are the most commonplace features used in the practice of science teachers. And as there are new digital inclusion programs that provide technological resources to schools with public funds, therefore, is the disuse of existing equipment, with no due reframing and transition in the pedagogical use of such resources in the teaching practice. These findings, in addition to forming themselves into obstacles to critical and innovative use of ICT in school education, point out the importance of teacher training in digital inclusion setting. Arising from the findings was prepared a proposal for Teacher Training, as a contribution to the learning process of science teachers from the final years of elementary school, aimed at integrating the educational laptop PROUCA, with emphasis on developing educational activities supported in the use of educational technology to streamline teaching practices.